Full body problem! Animation control for virtual reality characters - Huiskonen, Jukka (My University, 2018)
This thesis aims to produce a solution which can create motion for full body virtual characters from the input of a typical virtual reality device and illustrates the issues when mapping the input motion from a virtual reality device to a full body character, an issue which is titled the ’Full Body Problem.’ The technical part of the thesis is created using Unity3D, a game engine. The animations used as a data source for the solution were a combination of motion capture animations created in Aalto MotionLab and premade clips from Unity Technologies. The written part explores the theoretical background for animating virtual characters and controlling them in real-time applications using various animation control methods. The definition of the Full Body Problem is introduced and discussed. An overview of the different technical parts is presented before an evaluation using a side-by-side comparison between the user motion and the motion created by the solution. The result of this thesis is a technical solution which produces relatively natural-looking motion of a virtual character from the user’s motion. The solution is controlled by a typical virtual reality device. The results provide insights for researchers and developers looking to develop similar systems. In conclusion, using a hybrid approach of direct mapping and animation control to solve the problem of limited tracking data is a solid basis for solving the Full Body Problem.

Tämän opinnäytetyön tavoitteena on tuottaa tekninen ratkaisu jolla kyetään ohjaamaan virtuaalisia hahmoja tyypillisen virtuaalitodellisuuslaitteen syötteellä. Tavoitteena on myös tuoda esille haasteita virtuaalisten hahmojen ohjauksessa. Opinnäytetyön tekninen osuus on luotu käyttäen pelimoottori Unity3D:tä. Ratkaisus- sa käytettyjen animaatioiden lähteenä on hyödynnetty Unity Technologies:n tarjoamia animaatioita, sekä Aalto-yliopiston MotionLab:ssä tuotettuja liikekaappausanimaatiota. Kirjallisessa osuudessa tarkastellaan virtuaalihahmojen animoinnin teoriataustaa ja niiden ohjaamista reaaliaikaisissa ohjelmissa. Osuudessä esitellään myös kokonaisen kehon ongelma sekä tehdään katsaus ratkaisun tekniseen osuuteen. Lopuksi arvioidaan ratkaisun kyky tuottaa luonnollisen näköistä liikettä vertaamalla rinnakkain käyttäjän ja ratkaisun tuottamia liikkeitä. Opinnäytetyön tuloksena on tekninen ratkaisu, joka pystyy tuottamaan suhteellisen luonnollisen näköistä liikettä virtuaalitodellisuuslaitteista saadun syötteen perusteel- la. Ratkaisu antaa monia oivalluksia tutkijoille ja kehittäjille, jotka ovat kehittämässä samankaltaisia ratkaisuja. Lopputuloksena hybridimalli, jossa käyttäjän syötteen suo- ranainen käyttö yhdistettynä animaatiokontrolliin osoittautui toimivaksi ratkaisuksi tilanteessa, missä käyttäjän syöte ei sisällä tietoa koko kehon liikkeistä.
Kokonaisen kehon ongelma! Tiedon ohjaamat hahmot virtuaalitodellisuudessa
Keywords: animation; data-driven animation; virtual reality; character control